2018
DOI: 10.3390/ijerph15030403
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Screen Viewing Times and Sociodemographic Factors among Pregnant Women: A Cross-Sectional Survey in China

Abstract: Objectives: This study aimed to assess the prevalence of prolonged television, computer, and mobile phone viewing times and examined related sociodemographic factors among Chinese pregnant women. Methods: In this study, a cross-sectional survey was implemented among 2400 Chinese pregnant women in 16 hospitals of 5 provinces from June to August in 2015, and the response rate of 97.76%. We excluded women with serious complications and cognitive disorders. The women were asked about their television, computer, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Various factors may affect the choice of postpartum DP (e.g., age, gender, and economic level) ( 30 , 33 ), but the effect of mode of delivery on postnatal DP has attracted limited attention. This study found no association between traditional DP and delivery mode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various factors may affect the choice of postpartum DP (e.g., age, gender, and economic level) ( 30 , 33 ), but the effect of mode of delivery on postnatal DP has attracted limited attention. This study found no association between traditional DP and delivery mode.…”
Section: Discussionmentioning
confidence: 99%
“…Educational level was recorded as two categories: secondary education or below (senior high school or below) and tertiary education (university or above). The average monthly household income was categorized as <¥4,500, ¥4,500–¥9,000 or >¥9,000 ( 30 ). Dietary caregivers were divided into three categories, including self/husband, in-laws/parents and maternity matron/nanny.…”
Section: Methodsmentioning
confidence: 99%
“…Pregnancy was excluded because pregnant females often attempt to adopt healthier behaviors and physiologic changes associated with pregnancy impact behaviors (e.g., nausea, food cravings). [59][60][61] The original data collection received Institutional Review Board approval, and permission to conduct secondary analyses was approved by the Emory University Institutional Review Board.…”
Section: Study Populationmentioning
confidence: 99%
“…Prolonged exposure to electronic screen is also very common in pregnant women. A cross-sectional survey conducted in 2015 indicated that about 25.1% reported prolonged television viewing (≥ 2 h/d), 20.6% reported prolonged computer viewing (≥ 2 h/d), and 62.6% reported prolonged mobile phone viewing (≥ 1 h/d) [ 11 ]. A case-control study carried out in 2019 showed that the median using time of smartphone and computer among healthy pregnant women was 5.5 and 3.0 h/day, respectively [ 12 ].…”
Section: Introductionmentioning
confidence: 99%